Drought-Stressed Tomato Plants Trigger Bottom-Up Effects on the Invasive Tetranychus evansi. - Miguel G Ximénez-Embún; Félix Ortego; Pedro Castañera (PLoS ONE, 2016)
Climate change will bring more drought periods that will have an impact on the irrigation practices of some crops like tomato, from standard water regime to deficit irrigation. This will promote changes in plant metabolism and alter their interactions with biotic stressors. We have tested if mild or moderate drought-stressed tomato plants (simulating deficit irrigation) have an effect on the biological traits of the invasive tomato red spider mite, Tetranychus evansi. Our data reveal that T evansi caused more leaf damage to drought-stressed tomato plants (≥1.5 fold for both drought scenarios). Mite performance was also enhanced, as revealed by significant increases of eggs laid (≥2 fold) at 4 days post infestation (dpi), and of mobile forms (≥2 fold and 1.5 fold for moderate and mild drought, respectively) at 10 dpi. The levels of several essential amino acids (histidine, isoleucine, leucine, tyrosine, valine) and free sugars in tomato leaves were significantly induced by drought in combination with mites. The non-essential amino acid proline was also strongly induced, stimulating mite feeding and egg laying when added to tomato leaf disks at levels equivalent to that estimated on drought-infested tomato plants at 10 dpi. Tomato plant defense proteins were also affected by drought and/or mite infestation, but T. evansi was capable of circumventing their potential adverse effects. Altogether, our data indicate that significant increases of available free sugars and essential amino acids, jointly with their phagostimulant effect, created a favorable environment for a better T. evansi performance on drought-stressed tomato leaves. Thus, drought-stressed tomato plants, even at mild levels, may be more prone to T evansi outbreaks in a climate change scenario, which might negatively affect tomato production on area-wide scales.